Kapasitas SDM Aparatur sebagai Penentu Efektivitas Perencanaan Pembangunan Desa: Studi di Desa Plalangan - Kuny Mufida; Nabila Rinty Mafasy; Ghefira Nurfatimah; Sheila Ramadana; Siti Nur Urifah; Prillinaya Yudhistira; Oryza Ardhiarisca (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Village development planning requires competent apparatus to ensure that programs are properly formulated and implemented. This study aims to analyze the constraints of apparatus human resource capacity in the planning process of Plalangan Village. A descriptive qualitative method was applied through interviews with village officials and head of BPD, supported by analysis of RPJMDes and RKPDes documents. The results show that planning remains suboptimal due to limited technical competence, insufficient training, weak data management, and low community participation. Moreover, the apparatus still struggle to prepare systematic planning documents aligned with the budget. The study highlights the importance of strengthening apparatus capacity to achieve effective and accountable village development planning.